Practical Aspects of Functional Magnetic Resonance Imaging in Children - Bernal, Byron (Journal of Pediatric Neurology, 2021)
Functional magnetic resonance imaging (fMRI) has become a broadly accepted presurgical mapping tool for pediatric populations with brain pathology. The aim of this article is to provide general guidelines on the pragmatic aspects of performing and processing fMRI, as well as interpreting its results across children of all age groups. Based on the author's accumulated experience of more than 20 years on this specific field, these guidelines consider many factors that include the particular physiology and anatomy of the child's brain, and how specific peculiarities may pose disadvantages or even certain advantages when performing fMRI procedures. The author carefully details the various challenges that the practitioner might face in dealing with limited volitional behavior and language comprehension of infants and small children and remedial strategies. The type and proper choice of task-based paradigms in keeping with the age and performance of the patient are discussed, as well as the appropriate selection and dosage of sedative agents and their inherent limitations. Recommendations about the scanner and settings for specific sequences are provided, as well as the required devices for appropriate stimulus delivery, response, and motion control. Practical aspects of fMRI postprocessing and quality control are discussed. Finally, given the relevance of resting-state-fMRI for use in noncooperative patients, a praxis-oriented guide to obtain, classify, and understand the spontaneous neural networks (utilizing independent component analysis) is also provided. The article concludes with a thorough discussion about the possible pitfalls at different stages of the fMRI process.
Keywords: fMRI; epilepsy; intractable epilepsy; pediatric; resting state